2016
DOI: 10.1002/ece3.2014
|View full text |Cite
|
Sign up to set email alerts
|

Incongruent range dynamics between co‐occurring Asian temperate tree species facilitated by life history traits

Abstract: Postglacial expansion to former range limits varies substantially among species of temperate deciduous forests in eastern Asia. Isolation hypotheses (with or without gene flow) have been proposed to explain this variance, but they ignore detailed population dynamics spanning geological time and neglect the role of life history traits. Using population genetics to uncover these dynamics across their Asian range, we infer processes that formed the disjunct distributions of Ginkgo biloba and the co‐occurring Cerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 68 publications
2
18
0
Order By: Relevance
“…Distribution range modeling linked with climatic fluctuations indicates that seasonal aridity more than temperature was a constraining factor (Huang et al 2015 ). Cenozoic co-occurrence of Ginkgo and Cercidiphyllum in disturbed streamside environments suggests prolonged conservation of their habitats (Zhao et al 2016 ). Molecular phylogeography, niche modeling, paleoclimatology, and life-history traits reveal an even more dynamic geographic history through glaciations.…”
Section: Living Fossils: a Biological Research Programmentioning
confidence: 99%
See 1 more Smart Citation
“…Distribution range modeling linked with climatic fluctuations indicates that seasonal aridity more than temperature was a constraining factor (Huang et al 2015 ). Cenozoic co-occurrence of Ginkgo and Cercidiphyllum in disturbed streamside environments suggests prolonged conservation of their habitats (Zhao et al 2016 ). Molecular phylogeography, niche modeling, paleoclimatology, and life-history traits reveal an even more dynamic geographic history through glaciations.…”
Section: Living Fossils: a Biological Research Programmentioning
confidence: 99%
“…Finer-scale studies reveal incongruent episodes of retreat, colonization, and expansion linked to changes in preferred habitats, as well as regional temperature and aridity fluctuations, topography, and hydrology. G. biloba's more restrictive, disjoint distribution relative to C. japonicum may relate to longer generation times, more climatically vulnerable reproductive periods, or more limited dispersal of its fleshy seeds compared to wind dispersal (Zhao et al 2016 ), implicating population demographic and life-history traits as potential explanations.…”
Section: Living Fossils: a Biological Research Programmentioning
confidence: 99%
“…In our previous contribution analyzing range dynamics between co-occurring Asian temperate trees from temperate deciduous forests [ 16 ], we elaborated on the relevance of three competing hypotheses that may explain the variation in the degree of expansion to former range limits in eastern Asia. The first hypothesis, introduced by Qian & Ricklefs [ 13 ], postulates that during glacial periods populations merged and admixed at lower elevations (isolation with admixture).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown strong evidence that glacial cooling has led to large range contractions in surviving tree species in Europe, albeit a subset of the more hardy species remained relatively widespread (Svenning, Normand, & Kageyama, ; Willis & Andel, ). Although less severe, many tree species have also exhibited range contractions during glacial maxima in North America (Bell, Bradford, & Lauenroth, ; Ordonez & Williams, ) and East Asia (Ni, Cao, Jeltsch, & Herzschuh, ; Zhao et al, ). These dynamics still shape diversity patterns within the regions, affecting endemism (Feng, Mao, Sandel, Swenson, & Svenning, ; Svenning & Skov, ), phylogenetic structure (Ma, Sandel, & Svenning, ) and even functional diversity (Ordonez & Svenning, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although less severe, many tree species have also exhibited range contractions during glacial maxima in North America (Bell, Bradford, & Lauenroth, 2014;Ordonez & Williams, 2013) and East Asia (Ni, Cao, Jeltsch, & Herzschuh, 2014;Zhao et al, 2016). These dynamics still shape diversity patterns within the regions, affecting endemism (Feng, Mao, Sandel, Swenson, & Svenning, 2016;Svenning & Skov, 2007), phylogenetic structure (Ma, Sandel, & Svenning, 2016) and even functional diversity .…”
Section: Climate Change and Trees In Europementioning
confidence: 99%